Analisis Pengaruh Bencana Gempa Bumi dan Tsunami di Donggala dan Palu terhadap Return Saham Sektoral - Suherniati, Suherniati; Ismail, Andy (Universitas Darwan Ali, 2020)
This research was for examining the impact of the earthquake and tsunami disaster in Donggala and Palu that occurred on September 28, 2018, against sectoral stock returns. The examined sectors are consumer goods sector, finance sector, property, real estate and building construction sector, and trade sector. The observation period used in this study for 100 exchange days consisted of 50 days before the disaster, 1 day during the disaster, and 49 days after the disaster. Samples were taken from 20 July 2019 to 6 December 2019. The research used several research windows, namely the day of the disaster, 2 days of the disaster, 3 days of the disaster, 6 days of the disaster, 10 days of the disaster, and 14 days of the disaster. Variable control is the Kurs and IHSG return. The research method uses multiple linear regression. The results of the study show that the facts that occurred in Donggala and Palu did not affect the sectors discussed.